2015
DOI: 10.4102/curationis.v38i2.1523
|View full text |Cite
|
Sign up to set email alerts
|

Nurse educators’ experiences of case-based education in a South African nursing programme

Abstract: BackgroundA school of nursing at a university in the Western Cape experienced an increase in student enrolments from an intake of 150 students to 300 students in the space of one year. This required a review of the teaching and learning approach to ensure that it was appropriate for effective facilitation of large classes. The case-based education (CBE) approach was adopted for the delivery of the Bachelor of Nursing programme in 2005.AimThe aim of the study was to explore nurse educators’ experiences, current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The majority of nurse educators in this study suggested the case study and role play as the best method of teaching. In this respect, Daniels and colleagues (31) Stated that role-playing as a method of teaching is an excellent way for students to participate actively. Roleplaying helps students learn clinical decision-making skills and can be used to dramatize difficulties in troubled nursing situations.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of nurse educators in this study suggested the case study and role play as the best method of teaching. In this respect, Daniels and colleagues (31) Stated that role-playing as a method of teaching is an excellent way for students to participate actively. Roleplaying helps students learn clinical decision-making skills and can be used to dramatize difficulties in troubled nursing situations.…”
Section: Discussionmentioning
confidence: 99%
“… 40 - 42 For the different obstacles faced by nursing students in case implementation, it’s necessary to point out their own shortcomings and the direction of making up later. 43 Therefore, in the cultivation of ability of nursing students, it is necessary to take the implementation and communication ability as 2 important evaluation indicators to measure in the ability assessment of nursing students. 44 At the same time, in nursing skill assessment, it is necessary to increase the proportion of the performance of nursing evaluation and nursing communication, making it more in line with the social needs of personnel training.…”
Section: Discussionmentioning
confidence: 99%
“…18,44,49 This was identified as being important to ensure consistency across multiple classes being run by different facilitators, as well as adapting facilitators with the specific skills required to facilitate CBL sessions. 50 Some facilitators, however, are resistant to change as they are more familiar with the traditional role of teachers. 51 Of particular concern are the subversive facilitators who do not believe in the philosophy of CBL and AL, and who might subtly or overtly communicate to students that they are receiving lower quality education.…”
Section: Discussionmentioning
confidence: 99%